Significant associations between lipoprotein(a) and corrected apolipoprotein B-100 levels in African-Americans - Enkhmaa, Byambaa (2014)
OBJECTIVES: Lipoprotein(a), Lp(a), represents an apolipoprotein (apo) B-carrying lipoprotein, yet the relationship between Lp(a) and apoB levels has not been fully explored. METHODS: We addressed the relationship between Lp(a) and apoB-containing lipoprotein levels in 336 Caucasians and 224 African-Americans. Our approach takes unique molecular properties of Lp(a) as well as contribution of Lp(a) to the levels of these lipoproteins into account. RESULTS: Levels of total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), apoB and apoB/apoA-1 did not differ across ethnicity. African-Americans had higher levels of Lp(a) and high-density lipoprotein cholesterol and lower triglyceride levels compared to Caucasians. Lp(a) levels were correlated with levels of TC (p<0.005), LDL-C (p<0.001), apoB (p<0.05) or apoB/apoA-1 (p<0.05) in both ethnic groups. These associations remained significant only in African-Americans after adjustments for the contribution of Lp(a)-cholesterol or Lp(a)-apoB. Furthermore, taking Lp(a)-apoB into account, allele-specific apo(a) levels were significantly associated with apoB levels and the apoB/apoA-1 ratio in African-Americans. The latter associations in African-Americans remained significant for allele-specific apo(a) levels for smaller apo(a) sizes (<26 K4 repeats), after controlling for the effects of age, sex, and BMI. CONCLUSIONS: Although TC, LDL-C, and apoB levels were comparable between African-Americans and Caucasians, the associations of these parameters with Lp(a) and allele specific apo(a) levels differed between these two ethnic groups. In African-Americans, apoB and apoB/apoA-1 remained consistently and positively associated with both Lp(a) and allele-specific apo(a) levels after adjustments for the contribution of Lp(a)-apoB. The findings suggest an interethnic difference with a closer relationship between Lp(a) and apoB among African-Americans.